Time to a tuberculosis treatment cure and its predictors among tuberculosis patients at public health facilities in Arba minch town, South Ethiopia: A retrospective cohort study - Dereje Dana Zeruma; Mesfin Kote; Eshetu Zerihun; Getahun Gedabo; Biruk Wogayehu (BMC Infectious Diseases)
Abstract Introduction The WHO’s 2024 Global tuberculosis (TB) Report shows that TB causes 1.25 million deaths annually, including 161,000 TB-Human Immunodeficiency Virus (HIV) infections. It affects 10.6 million people, mainly in Asia and Africa, 75% of whom are in the economically active age group of 15–54 years. Treatment interruptions hinder efforts to eliminate TB by 2030. According to a recent systematic review conducted using Ethiopian studies indicated that the pooled prevalence of TB treatment cure rate was 33.9%. There is a lack of evidence on time to TB treatment cure in Ethiopia using survival analysis. Objective This study aimed to determine the time to TB treatment cure and its predictors among TB patients from January 2021 to December 2023 at public health facilities in Arba Minch town. South Ethiopia. Method An institution-based retrospective cohort study was conducted among 628 selected TB patients who were admitted to the TB care unit at Arba Minch General Hospital, Dilfana Primary Hospital, and both health centers from 2021 to 2023. A Kaplan Meier survival curve was fitted to test the survival time. The Cox proportional hazards model was used to identify predictors with TB treatment cure. Significance was considered at a p value ≤ 0.05 with an adjusted hazard ratio (AHR) 95% CI in the multivariate analysis. Results Out of the 628 patients whose records were analyzed, the median time to cure was 162 days. The significant predictors of time to TB cure included being male (AHR 0.3, 95% CI: 0.35–0.95), history of TB treatment (AHR 0.56, 95% CI: 0.35–0.95), normal BMI (AHR 1.04, 95% CI: 1.32–1.49) and attending at secondary heath facility (AHR 1.69, 95% CI: 1.40–2.00). Conclusions Socio-demographic and clinical related factors were found to be independent predictors of time to cure. TB control programs should adopt gender-sensitive approaches to address delayed cure in male patients, integrate nutritional assessment into care and strengthen primary health facilities.